2018
DOI: 10.3892/etm.2018.5762
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of apoptosis induction associated with ERK1/2 upregulation via goniothalamin in melanoma cells

Abstract: Abstract. The present study aimed to investigate the effect of goniothalamin on apoptosis induction in the A375 melanoma cell line. Melanoma is a type of skin cancer with increased prevalence and no potential standard treatment. Goniothalamin is a plant, bioactive styrly-lactone, which has various bioactivities including anti-microbial, anti-inflammatory and anti-cancer. Apoptosis induction by goniothalamin has been studied in numerous cancer cell lines, however not in the melanoma cell line A375. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
5
8
0
Order By: Relevance
“…Several plant extracts have shown to decrease MMP in a variety of cancer cell lines and this property has also been implicated in the apoptosis and our current results are in consistent with these reports. Furthermore, chromatin condensation is also reported as an indicator of apoptotic nuclei . In the present study, Hoechst staining confirmed the presence of nuclei with bright fluorescence indicating the chromatin condensation and nuclear fragmentation in SC treated HepG2 cells.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Several plant extracts have shown to decrease MMP in a variety of cancer cell lines and this property has also been implicated in the apoptosis and our current results are in consistent with these reports. Furthermore, chromatin condensation is also reported as an indicator of apoptotic nuclei . In the present study, Hoechst staining confirmed the presence of nuclei with bright fluorescence indicating the chromatin condensation and nuclear fragmentation in SC treated HepG2 cells.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, chromatin condensation is also reported as an indicator of apoptotic nuclei. [27][28][29] In the present study, Hoechst staining confirmed the presence of nuclei with bright fluorescence indicating the chromatin condensation and nuclear fragmentation in SC treated HepG2 cells.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Additionally, we detected elevated levels of ERK1/2 accompanied with the overexpression of S100A16 . ERK1/2 was reported to activate proapoptotic proteins in the BCL2 family and deactivate AKT signalling pathways, leading to apoptosis induction (Tangchirakhaphan et al , ). By suppressing the phosphorylation of ERK1/2, the anti‐proliferation and pro‐apoptosis caused by overexpression of S100A16 could be apparently attenuated.…”
Section: Discussionmentioning
confidence: 99%